A review of forward osmosis membrane fouling: types, research methods and future prospects. Issue 1 (1st January 2017) - Li, Lan; Liu, Xing-peng; Li, Hui-qiang
ABSTRACT: Forward osmosis (FO) is becoming a versatile platform membrane-based technology, which has received increasing attention recently. Despite several studies have proved that membrane fouling is less detrimental to FO performance than other membrane processes, membrane fouling is also one of the major drawbacks for FO and has raised extensive concern over the recent years. Moreover, fouling layer formation mechanisms and fouling control ways often significantly different resulted from diverse types of foulants. This paper provides an up-to-date review of the FO membrane fouling behaviors and pays special attention to various foulants during the FO operation. For the sake of investigating fouling behaviors in FO processes, a clear cognition of membrane fouling monitoring methods is a prerequisite and foundation for researchers. Therefore, we briefly summarize the advanced membrane fouling research techniques based on the indicators for membrane fouling. Besides, we demonstrate the differences between FO and reverse osmosis in the various types of membrane fouling since they help guide future investigations in FO membrane fouling. Furthermore, the challenges still faced and perspectives for the future of investigations on FO membrane fouling have been discussed.